Kontribusi Khutbah Jum'at dalam Pembinaan Kerukunan Antar Umat Beragama di Masyarakat (Studi Kasus di Desa Anamina Kecamatan Manggelewa Kabupaten Dompu) - Fitriani Fitriani (LP2M STIT Palapa Nusantara, 2017)
Friday's sermon is one means to create religious harmony. Through the Friday sermon the community can be given an understanding of the importance of living in harmony between religious people. Based on the results of the exposure in this journal it can be concluded that the background of the emergence of harmony between religious communities are: (1) The educational factor, most of the population who have received the education became more aware of the importance of maintaining harmony of life among religious people. It proves that their understanding of religious differences is no longer superficial, so the differences are not a pretext to overthrow each other. But it isall used as a means to be able to establish cooperation. (2) Conditions of environment, circumstances and circumstances conducive environment, in the sense that there is rarely and even never a conflict in the name of religion. It drove them away from the influence of secularism and sara issues that could lead to division. (3). Geographical location, viewed from geographical location, village Anamina Kec. Manggelewa Kab. Dompu which is located a bit isolated in the suburbs makes their lives become more secure and comfortable because it is protected from the harsh influence of city life that more presenting the principle of living individualism.